2022
DOI: 10.1007/s44197-022-00040-w
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Tuberculosis Screening of Resident Visa Applicants in Low TB Incidence Settings: Experience from Oman

Abstract: Introduction For Oman, a country targeting tuberculosis (TB) elimination, TB among expatriates is a major challenge. Thus, screening for active TB using chest X-ray was made mandatory for expatriates’ residency renewals. Objective To estimate the incidence of bacteriologically confirmed TB and assess impact of chest X-ray based TB screening among expatriates in Muscat Governorate. Methods Applicants for residency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Testing for interferon-gamma release assay among 1,042 applicants for visa renewal in 2019, in Sohar governorate, showed a high prevalence of positive cases among expatriates from Asia (21%) and Africa (31%), indicative of LTB ( 38 ). Similarly, a survey of 501,290 expatriates, for visa renewal in 2018–2020, in Muscat governorate, revealed an LTB rate of 10.6 per 100,000 applicants ( 4 ). This is consistent with the findings of 158 out of 97,100 X-ray results of expatriates in Oman, with presumptive pulmonary TB, in 2018 ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testing for interferon-gamma release assay among 1,042 applicants for visa renewal in 2019, in Sohar governorate, showed a high prevalence of positive cases among expatriates from Asia (21%) and Africa (31%), indicative of LTB ( 38 ). Similarly, a survey of 501,290 expatriates, for visa renewal in 2018–2020, in Muscat governorate, revealed an LTB rate of 10.6 per 100,000 applicants ( 4 ). This is consistent with the findings of 158 out of 97,100 X-ray results of expatriates in Oman, with presumptive pulmonary TB, in 2018 ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of 158 out of 97,100 X-ray results of expatriates in Oman, with presumptive pulmonary TB, in 2018 ( 38 ). Thus, the diagnosed TB cases in Oman among the expatriate community are most probably a result of the reactivation of LTB acquired in their country of origin ( 4 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with the clinical picture, radiographic chest assessment has high sensitivity in detecting TB [6,7]. Thus, it is standard practice to utilize chest X-rays as part of the formal TB screening for new immigrant workers across various primary healthcare facilities in Saudi Arabia and the Gulf region [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…TB data is sparse from Oman (33-36). The rates of all forms of TB notification have steadily decreased to <100 cases per million since 1991 (37). One study conducted in 2022 found that from 501,290 visa applicants screened, 436 (0.09%) had X-ray findings suggestive of TB.…”
Section: Introductionmentioning
confidence: 99%